Cultures of Witchcraft in Europe from the Middle Ages to the Present (Cham : Springer International Publishing, 2018)
This volume is a collection based on the contributions to witchcraft studies of Willem de Blécourt, to whom it is dedicated, and who provides the opening chapter, setting out a methodological and conceptual agenda for the study of cultures of witchcraft (broadly defined) in Europe since the Middle Ages. It includes contributions from historians, anthropologists, literary scholars and folklorists who have collaborated closely with De Blécourt. Essays pick up some or all of the themes and approaches he pioneered, and apply them to cases which range in time and space across all the main regions of Europe since the thirteenth century until the present day. While some draw heavily on texts, others on archival sources, and others on field research, they all share a commitment to reconstructing the meaning and lived experience of witchcraft (and its related phenomena) to Europeans at all levels, respecting the many varieties and ambiguities in such meanings and experiences and resisting attempts to reduce them to master narratives or simple causal models. The chapter 'News from the Invisible World: The Publishing History of Tales of the Supernatural c.1660-1832' is available open access under a CC BY 4.0 license at link.springer.com.
Introduction; Jonathan Barry, Owen Davies and Cornelie Usborne -- Contested Knowledge: The Historical Anthropologist's Approach to European Witchcraft; Willem de Blécourt -- Witches and Devil's Magic in Austrian Demonological Legends; Christa Agnes Tuczay -- Hanna Dyâb's Witch and the Great Witch Switch; Ruth Bottigheimer -- The Mirror of the Witches (1600). A German tragedy in context; Rita Voltmer -- Unravelling the Myth and Histories of the Weighing Test at Oudewater: the case of Leentje Williams; Machteld Löwensteyn -- The North Sea as a Crossroads of Witchcraft Beliefs: the limited importance of political boundaries; Hans de Waardt -- "Kind in words and deeds, but false in their hearts". Fear of evil conspiracy in late sixteenth-century Denmark; Louise Nyholm Kallestrup -- "Ein gefehrlich Ding, darin leichtlich zuviel geschieht" (A dangerous thing in which too much happens easily): The end of village witch-trials in the Saar region; Eva Labouvie -- News from the Invisible World: the publishing history of tales of the supernatural c.1660-1832; Jonathan Barry -- Researching Reverse-Witch Trials in Nineteenth- and Early Twentieth-Century England; Owen Davies -- The Catechism of Witch Lore in Twentieth-Century Denmark; Gustav Henningsen -- Magic and Counter-Magic in Twenty-First-Century Bosnia; Mirjam Mencej -- Index.
History
text file PDF
Keywords: Europe-History-476-1492.; Europe-History-1492-.; Civilization-History.; Social history